Religion in companies: conflicts and solutions - Rodríguez Moya, Almudena (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Recessions, like the present, can be seen, from the business perspective, as a curse or become an opportunity. But when the economic situation changes, the issue of religious beliefs and practices in business will be located, in the light of what is already happening in other countries, in the forefront of issues that future leaders business will face. Companies are not, or should not be— beyond the changes that occur in the societies in which they operate and the management of diversity is a matter of great interest to Human Resources.